2009
DOI: 10.1017/s0024282909990211
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic study of theMicarea prasinagroup shows thatMicarea micrococcaincludes three distinct lineages

Abstract: The phylogeny of the Micarea prasina group was investigated using mitochondrial small subunit ribosomal DNA sequences from 14 taxa representing this group, four other members of the genus Micarea, and Psilolechia lucida as an outgroup. A total of 31 new mtSSU rDNA sequences were generated, including 10 from the M. micrococca complex. Bayesian, maximum parsimony (MP) and maximum likelihood (ML) methods were used to analyse the data. The results show that M. micrococca is not monophyletic and forms three strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(95 citation statements)
references
References 32 publications
10
85
0
Order By: Relevance
“…Phylogenetic inferences from mtSSU sequences position M. herbarum in an unsupported clade within the strongly supported M. prasina group, together with both lineages referred to as M. prasina and M. nowakii, a species described from Poland (Czarnota 2007 The position of the two accessions of M. herbarum in our phylogenetic tree points to a relationship between M. herbarum and M. nowakii, or even that M. herbarum cannot be distinguished from M. nowakii. Among the mtSSU sequences published by Czarnota & Guzow-Krzemińska (2010) for M. nowakii, one accession (Poland, P. Czarnota 4634, GPN) is resolved with strong support as closely related to M. herbarum. We found that this collection represents M. herbarum (no micareic acid detected by TLC); a further collection (Poland, P. Czarnota 3464, GPN) might represent either a further species in that group, or a variant of M. herbarum.…”
Section: Resultsmentioning
confidence: 96%
“…Phylogenetic inferences from mtSSU sequences position M. herbarum in an unsupported clade within the strongly supported M. prasina group, together with both lineages referred to as M. prasina and M. nowakii, a species described from Poland (Czarnota 2007 The position of the two accessions of M. herbarum in our phylogenetic tree points to a relationship between M. herbarum and M. nowakii, or even that M. herbarum cannot be distinguished from M. nowakii. Among the mtSSU sequences published by Czarnota & Guzow-Krzemińska (2010) for M. nowakii, one accession (Poland, P. Czarnota 4634, GPN) is resolved with strong support as closely related to M. herbarum. We found that this collection represents M. herbarum (no micareic acid detected by TLC); a further collection (Poland, P. Czarnota 3464, GPN) might represent either a further species in that group, or a variant of M. herbarum.…”
Section: Resultsmentioning
confidence: 96%
“…In many cases, the discovery of cryptic lineages leads to discovery of other subtle, previously unknown characters that characterize those lineages. Such characters may include differences in ecology, chemistry, physiology, microstructures, biogeography, or even a combination of these traits (Arup and Åkelius 2009;Czarnota and Guzow-Krzemińska 2010;Lendemer 2011;Parnmen et al 2012;Pillon et al 2014;Vondrák et al 2009;Yost et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Distribution in Fennoscandia and Baltic countries: Norway, Sweden, Finland (Nordin et al, 2011), Lithuania (Motiejūnaitė, 1999). Differs from other species by black stalked pycnidia with walls dull greenish to olive-brown in squash preparation, K-or K+ green intensifying (Coppins, 1983;Czarnota, 2007 (Nordin et al, 2011), Estonia, Lithuania (Czarnota, Guzow-Krzemińska, 2010). Thalli contain methoxymicareic acid.…”
Section: Methodsmentioning
confidence: 99%